Transscleral Diode Laser Cyclophotocoaglation for Refractory Glaucoma - Syed Fawad Rizvi, Munira Shakir, Syeda Aisha Bokhari, Shakir Zafar, Zeeshan Kamil (Pakistan Journal of Ophthalmology, 2018)
Purpose: To assess the efficacy of contact transscleral cyclophotocoagulation for refractory glaucoma. Material and Methods: The study was conducted in L.R.B.T Free Base Eye Hospital from January 2008 to December 2010. All patients included in the study were diagnosed with refractory glaucoma with uncontrolled intraocular pressure on medical treatment. The study included 32 eyes of 30 patients who underwent transscleral diode laser cyclophotocoagulation (TSDLCPC) therapy. Mean follow up was 21 months. Outcome measures were intraocular pressure control and assessment of visual acuity and complications. Results: The study included 32 eyes of 30 patients with refractory glaucoma who were treated with transscleral diode laser cyclophotocoagulation. There was significant decrease in intraocular pressure from 52.2 to 18.4 mmHg, with mean percentage reduction of 64.7%. Visual acuity remained stable in 28 (87.5%) eyes, improved in 3 (9.37%) eyes and deteriorated in 1 (3.12%) eye. Complications included early post procedure pain in 6 (26.6%) cases, moderate uveitis in 2 (6.6%) cases, hypotony in 4 (12.5%) cases, epithelial defect in 1 (3.12%) case and hyphema in 1 (3.12%) case. Re-treatment was required in 10 (31.25%) patients, which included 6 (20.25%) eyes with neovascular glaucoma, 2 (6.255) eyes with silicone oil and 2 (6.25%) eyes with post-traumatic glaucoma. Conclusion: Transscleral diode laser cyclophotocoagulation is a safe and effective procedure for patients with refractory glaucoma, although re-treatment sessions may be required.